Building orientation selection for thermal comfort fieldwork measurement: a systematic literature review / Noor Anis Afifa Shamsu Kamal Bahrin, Asniza Hamimi Abdul Tharim and Azhan Abdul Aziz - Shamsu Kamal Bahrin, Noor Anis Afifa; Abdul Tharim, Asniza Hamimi; Abdul Aziz, Azhan (2021)
Building orientation is a significant design consideration, mainly with regard to solar radiation and wind. The orientation of buildings has an important influence on the side of thermal comfort. In predominantly hot humid regions like Malaysia which receives sunlight all year around, buildings should be oriented to minimize solar gain and maximize the comfort. Therefore, it is crucial for residential buildings to be oriented in the best orientation to get more comfort for its occupants since most of the people spend their time inside the house. The overall aim of the study is to determine the effects of orientation towards thermal comfort condition and occupants’ satisfaction in low cost detached housing while the purpose of this paper is to review the research method of determining the orientation that will be carried out during the fieldwork measurement of thermal comfort. There are various orientations used by previous researchers. Hence, this paper will examine them to get the best solution in deciding the orientation for the thermal comfort fieldwork experiment, using a Systematic Literature Review (SLR).